Does low intensity direct current affect open fracture wound healing? - Yoyos Dias Ismiarto; Kemas Abdul Mutholib Luthfi; Mahyudin Mahyudin; Adriel Benedict (Medicinski glasnik, 2020)
Aim: To explore the effects of a molecular pathway from the application of low-intensity direct current (LIDC) for wound healing through the pathway signalling growth factor and initiation of fibroblast activation. Methods: This randomized clinical trial included 32 patients with open fracture wounds who came to Hasan Sadikin Hospital in Bandung, Indonesia. The patients were divided in the control and the treatment group. Extensive assessment of wound contractions, FGF2 and FGF7 levels, and fibroblast expression were evaluated before and after the treatment. Results: This study showed a better wound area repair in the treatment group than the standard group, 3.17±0.11 and 0.78±0.07, respectively. The increase of FGF-2 level (42.69±3.5 and 15.09±1.8, respectively), FGF-7 level (42.99±3.55 and 14.67±1.9, respectively), and fibroblast group expression (7.62±0.79 and 3.54±0.6, respectively) were found to be higher in the treatment group (p<0.05). Conclusion: Low-intensity direct current accelerates wound healing through the increase of growth factor and fibroblast activation.
Keywords: fibroblast; fibroblast growth factor 2; fibroblast growth factor 7; open fracture; wound healing